(untitled) (Research, Society and Development, 2021)
Objectives: The aim of this study was to describe the advantages and disadvantages of CTZ paste for the endodontic treatment of primary teeth. Literature review: Root canals of deciduous teeth have peculiar characteristics that make access and instrumentation difficult, such as: accentuated curvatures and high rates of accessory canals. The filling materials used in the endodontic treatment of primary teeth need to be reabsorbable, antimicrobial, allow filling and adhesion to the walls of the root canals, and must be easy to remove, characteristics that allow non-compromising for the child’s future permanent dentition. The technique of applying CTZ paste (chloramphenicol, tetracycline and zinc oxide eugenol) is considered easy, simple and can be performed in a single session, has antibacterial power, promoting stabilization of bone resorption and not causing tissue sensitivity. Furthermore, it does not require previous instrumentation of the root canal, regardless of the pulp diagnosis. Final considerations: The endodontic treatment performed in primary dentition has several limitations, such as its anatomy and the difficulty of performing an invasive treatment in a pediatric patient. The use of CTZ paste in pulp therapy for primary teeth allows the maintenance of endodontically treated teeth, without harming their permanent successors, so its use becomes an option for pulp treatment in pediatric dentistry, however, further studies are needed. work on the effectiveness of this obturator paste in the long term, helping to demystify such monitoring.